An asymmetric and theoretical approach to the Morita-Baylis-Hillman reaction using vinyl-1,2,4-oxadiazoles as nucleophiles - Chagas, Thaynan A. B; Piscelli, Bruno A; Santos, Hugo; Lima, Sâmia R; Cormanich, Rodrigo A; Fernandes, Fábio S; Coelho, Fernando (Organic & biomolecular chemistry, 2025)
In this work, we present the first enantioselective Morita-Baylis-Hillman reaction using a vinyl heterocycle as the nucleophilic partner. The reaction between vinyl-1,2,4-oxadiazoles and N -substituted isatins is catalyzed by β-isocupreidine (β-ICD), yielding compounds in up to 95% yield and up to 98 : 2 er. The enantioselectivity of the reaction was investigated through theoretical calculations, which allowed us to identify the factors influencing the enantioselectivity, explain the preference for the formation of the R enantiomer, and understand the low or absent enantioselectivity when an isatin containing a nitro group is employed. Moreover, the methodology developed enabled the synthesis of chiral analogues of the natural products phidianidine A and phidianidine B, offering unique opportunities to obtain structurally diverse chiral 1,2,4-oxadiazoles. We report an enantioselective Morita-Baylis-Hillman reaction using vinyl-1,2,4-oxadiazoles as nucleophiles. Computational studies provided insights into the observed enantioselectivity and helped to identify the factors controlling it.